2021
DOI: 10.21203/rs.3.rs-359374/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compensation or displacement of physical activity in children and adolescents—A systematic review of empirical studies

Abstract: Background: Regular physical activity during childhood and adolescence is associated with health benefits. Consequently, numerous health promotion programs for children and adolescents emphasize the enhancement of physical activity. However, the ActivityStat hypothesis states that increases in physical activity in one domain are compensated for by decreasing physical activity in another domain. Currently, little is known about how physical activity varies in children and adolescents within intervals of one and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…In summary the synthesis of the included studies revealed a tendency for compensatory behavior in intervention studies, which was similar to our results. Furthermore, the study did not find indicators for compensatory behavior for children and adolescents who regularly participated in organized sports 34 …”
Section: Discussionmentioning
confidence: 60%
“…In summary the synthesis of the included studies revealed a tendency for compensatory behavior in intervention studies, which was similar to our results. Furthermore, the study did not find indicators for compensatory behavior for children and adolescents who regularly participated in organized sports 34 …”
Section: Discussionmentioning
confidence: 60%